THE INFLUENCE OF GENERAL ALLOCATION FUNDS AND CAPITAL EXPENDITURES ON THE FINANCIAL PERFORMANCE OF REGENCY/CITY REGIONAL GOVERNMENTS IN EAST JAVA PROVINCE - Imami, Prima Rizki; Akbar, Fajar Syaiful (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research aims to analyze the influence of General Allocation Funds and Capital Expenditures on the financial performance of the Regency/City regional government of East Java Province in 2018-2022. The object of this research is 38 Regency/City Budget Realization Reports for East Java Province 2018-2022. This research data collection method uses documentation techniques by obtaining data from the official DJPK website of the Ministry of Finance. The research results reveal that the General Allocation Funds has a negative effect on the Financial Performance of Regency/City East Java Province in 2018-2022. Meanwhile, capital expenditure has a positive effect on the financial performance of districts/cities in East Java Province in 2018-2022